Úvod do ekologické problematiky - Jemelka, Petr (Masaryk University Press, 2021)
Title in English: Introduction to ecological issues. The textbook offers the characteristics of ecology as a scientific field. The next chapters deal with cultural ecology and nature conservation issues. It also includes a chapter on environmental ethics. The final part deals with issues of education.